The mental health and wellbeing survey of Australian optometrists. (20th April 2021) - Bentley, Sharon A; Black, Alex; Khawaja, Nigar; Fylan, Fiona; Griffiths, Amanda M; Wood, Joanne M
Abstract: Purpose: To investigate the prevalence of mental health conditions and burnout among practising optometrists in Australia. Methods: A cross‐sectional survey of registered practising Australian optometrists was undertaken over a three‐week period from mid‐November 2019. The survey comprised three well‐established mental health scales (Kessler Psychological Distress Scale [K10], Depression Anxiety Stress Scales [DASS‐21] and Maslach Burnout Inventory [MBI]) and an open‐ended question inviting comments. Results: Five hundred and five respondents completed the K10, representing 8.8% of registered optometrists in Australia; 466 completed all three scales. Prevalence of moderate to severe psychological distress (K10 ≥ 25) was 30.7% (95% CI 26.7%–34.7%), with similar findings for depression and anxiety (DASS‐21). Prevalence of high burnout, as indicated by MBI‐GS exhaustion was 56.1% (95% CI 51.7%–60.4%), cynicism 57.1% (95% CI 52.7%–61.5%) and professional efficacy 23.1% (95% CI 19.4%–26.8%). Optometrists aged ≤ 30 years were 3.5 times more likely to report moderate to severe psychological distress compared to optometrists aged >30 years (OR = 3.54, P < 0.001, 95% CI 2.38–5.25). The most frequently mentioned work‐related issues concerned retail pressures, workload and career dissatisfaction. Conclusions: The rates of mental health conditions and burnout reported by practising Australian optometrists were high compared with the general population and other health professionals. Younger age and burnout were significant risk factors for psychological distress. Interventions are required to address these issues, particularly for younger optometrists, and could include workplace modifications and building resilience to improve personal mental wellbeing and ensure patient safety.